Hubungan Self Regulation dengan Bedtime Procrastination pada Remaja yang Bermain Game Online - S., Fidila Azzahra; Rusli, Devi (Lembaga Yasin AlSys, 2024)
This study aims to determine the relationship between self regulation and bedtime procrastination in adolescents who play online games in Sawahlunto City. This study uses a quantitative approach with correlational method. The sample selection was 272 teenegers using purposive sampling technique. Bedtime procrastination scale measuring instrument adapted from S.Khairunnisa (2023) with 7 items. Self regulation measuring instrument adapted from Setiawan,B (2022) with 49 items from 3 aspects. Data analysis in this study, using product moment correlation terchniques with the help of SPSS.16 program. The results of this study found that there is a significant relationship between self regulation and bedtime procrastination with a negative direction, meaning that if self regulation is high, then bedtime procrastination is low, in adolescents who play online games in Sawahlunto City and vice versa.